Virtual screening of compounds from the patchouli oil of Pogostemon herba for COX-1 inhibition - Raharjo, Sentot Joko (Biomedical Informatics, 2013)
Our interest is to identify compounds from the patchouli oil of Pogostemon herba to inhibit the cyclooxygenase-1 (COX-1) enzyme activity. The data for the major compounds (alpha-patchouli alcohol isomer (CD521903, CD442384, and/or CD6432585), alphabulnusene, seychellene and alpha-guaiene) of patchouli oil were explored from the PubChem database. The compounds to COX-1 interactions were studied using the molecular docking tools Hex 6.12 and LeadIT2 Bisolve. The interactions were further visualized using the Chimera 1.7s viewer software tool. The analysis of the major compounds of patchouli oil showed that alpha-Patchouli alcohol (CD521903) binds to COX-1 at many active sites including: Leu223B, Asp228B, Leu237B, Arg332B, Trp138A, Glu139A, Ser142A, and Asn143A. Further analysis revealed that these binding sites are maintained by hydrogen bonds with Ser142A, Glu139A, and Asp228B. The interaction energy between COX-1 and alpha-patchouli alcohol (CD521903) is -6 kJ/mol (without solvent) and -15 kJ/ mol (with solvent DMSO). These theoretical data suggests alpha-patchouli alcohol as a potential inhibitor of the COX-1 enzyme. However, these observations should be investigated and confirmed using experimental evidence.